Comparative Analysis of the Yanbu’a and An-Nahdiyah Methods in Improving the Quality of Al-Qur’an Recitation - Tarissa Octaviani; Beko Hendro; Kiki Muhamad Hakiki; Ahsanu Nadiyya (Jurnal test, 2025)
The Qur'an learning method plays a crucial role in improving the quality of recitation among students. This study aims to analyze the comparison of the effectiveness of the Yanbu’a and An-Nahdiyah methods in improving the quality of Quranic recitation at Pondok Pesantren Tahfidzul Qur’an ‘Ibaadurrahman and Pondok Pesantren Darussalamah, Way Jepara District, East Lampung. This research uses a qualitative approach with a comparative study method. Data were collected through observation, in-depth interviews, and documentation studies of teachers and students in both pesantren. The analysis was conducted by comparing aspects of the teaching methods, accuracy of makharijul huruf, application of tajwid rules, as well as the speed and durability of the students’ memorization. The results show that the Yanbu’a method is more systematic in teaching makharijul huruf and tajwid, providing students with a more structured understanding of recitation rules before memorization. On the other hand, the An-Nahdiyah method emphasizes direct practice with a flexible approach, enabling students to read and memorize the Quran more quickly. The conclusion of this study shows that both methods have their respective advantages. Therefore, the choice of teaching method should be adjusted to the characteristics of the students and the educational goals of Quranic learning in each pesantren.